Governance and Performance: Publicly Listed Companies in Malaysia - Ponnu , Cyril H.; Ramthandin , Sarimah (Journal of Law and Governance, 2008)
This paper investigates the relationship between corporate governance practice (as indicated by corporate governance disclosure) and company’s financial performance. Certain corporate structures and practices were examined to determine if they have any effect on company’s performance. Corporate governance practices were assessed based on the level of disclosure made in the companies’ annual reports. For financial performance, stock price performance and return on equity (ROE) were used as proxies. Results show that there is a positive relationship between the corporate governance practices and company performance. Findings from this research could be used by regulators, investors, corporations and others who contend that good corporate governance is important for increasing firm’s performance and investor confidence.